A Model Study Of Copper Rougher Recovery Optimisation At PT Freeport Indonesia - S R Grano (The Southern African Institute of Mining and Metallurgy, 2007)
A fundamental model, which considers the subprocesses of particle collection by bubbles in flotation, is applied to two comprehensive flotation surveys in the rougher stages of C3 concentrator, PT Freeport Indonesia. The flotation surveys focused on the collection of: ? cell-by-cell and size-by-size metallurgical, ? cell hydrodynamic, and ? pulp and surface chemistry information. The two surveys were conducted at significantly different feed tonnages, giving rise to significantly different feed particle size distributions, pulp densities and mean pulp residence times. A series of model simulations are performed with the aim of quantifying changes in copper recovery, on both a size-by-size and unsized basis, with changes in values of the hydrodynamic parameters and hydrophobicity of the copper sulfide mineral. This was carried out in an effort to identify the most promising route to increase overall copper recovery in roughing. It was found that by increasing the hydrophobicity of the copper sulfide mineral surfaces it became possible to optimise cell hydrodynamics, which targeted increased fine (-12 µm) copper sulfide mineral recovery but without adversely affecting coarse (+150 µm) copper sulfide mineral recovery.